1997
DOI: 10.1007/s004840050056
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mean skin temperature formulas by infrared thermography

Abstract: To study the reliability of formulas for calculating mean skin temperature (Tsk), values were computed by 18 different techniques and were compared with the mean of 10,841 skin temperatures measured by infrared thermography. One hundred whole-body infrared thermograms were scanned in ten resting males while changing the air temperature from 40 degrees C to 4 degrees C. Local, regional average and mean skin temperatures were obtained using an image processing system. The agreement frequency, defined as the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(95 citation statements)
references
References 21 publications
2
89
1
3
Order By: Relevance
“…Cangar et al (2008) found that the comb had the highest temperature gradient while the wing had the lowest. The head and neck regions and perhaps some areas around the abdomen are poorly feathered, hence insulation is quite poor in these areas, and consequently the sensible heat flow is improved (Li and Yamamoto, 1991;Choi et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Cangar et al (2008) found that the comb had the highest temperature gradient while the wing had the lowest. The head and neck regions and perhaps some areas around the abdomen are poorly feathered, hence insulation is quite poor in these areas, and consequently the sensible heat flow is improved (Li and Yamamoto, 1991;Choi et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Roy and collaborators [16] performed a study in which thermography was used to analyze the time necessary for the temperature in the region of the spine to stabilize and suggested a minimum time of 8 min and maximum of 16 min for reliable measurements [16]. The recommended acclimatization time varies between studies of skin thermometry, with periods of 10 min [14,17], 15 min [8] and 20 min [4] suggested for the subject to remain at rest in a room with controlled temperature and humidity. This variation may be influenced by environmental conditions, especially by the temperature outside the test room.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of consensus [4,8,[14][15][16][17] makes it difficult to determine the optimal acclimatization protocol because each study recommends a different acclimatization period to achieve a stable T SK to ensure the homogeneity of results and allow consistent interpretation and comparison of results between studies. Consequently, the objective of this study was to identify the time required to achieve a stable T SK at rest in a group of young men and women.…”
Section: Introductionmentioning
confidence: 99%
“…Roy and collaborators (2006) performed a study in which thermography was used to analyze the time necessary for the temperature in the region of the spine to stabilize and suggested a minimum time of 8 minutes and maximum of 16 minutes for reliable measurements (Roy et al, 2006). The recommended acclimatization time varies between studies of skin thermometry, with periods of 10 minutes (Choi et al, 1997;Ferreira et al, 2008) 15 minutes (Zontak et al, 1998) and 20 minutes (Merla et al, 2010) suggested for the subject to remain at rest in a room with controlled temperature and humidity. This variation may be influenced by environmental conditions, especially by the temperature outside the test room.…”
Section: 2factors Influencing the Use Of Infrared Thermography Inmentioning
confidence: 99%
“…This variation may be influenced by environmental conditions, especially by the temperature outside the test room. This lack of consensus (Choi et al, 1997;Ferreira et al, 2008;Merla et al, 2010;Ring & Ammer, 2000;Zontak et al, 1998) makes it difficult to determine the optimal Introduction 16 acclimatization protocol because each study recommends a different acclimatization period to achieve a stable T sk to ensure the homogeneity of results and allow consistent interpretation and comparison of results between studies. A recent study by Bouzas Marins and collaborators has directly analysed the optimal acclimatisation time for IRT evaluation in humans.…”
Section: 2factors Influencing the Use Of Infrared Thermography Inmentioning
confidence: 99%